An Analysis of Challenges, and Prospects of Overcrowding and Heritage Small Island as a Tourism Destination: Pulau Lengkang, Batam Case Study - Suryawan, I Wayan Koko; Suhardono, Sapta; Septiariva, Iva Yenis; Adicita, Yosef; Prayogo, Wisnu (Institut Teknologi Sepuluh Nopember, 2024)
This paper explores Pulau Lengkang, an island near Batam City, known for its natural beauty and cultural heritage. It examines the impact of overcrowding on its aspiration to become a prominent tourism heritage destination. The main goal is to analyze the strengths, weaknesses, opportunities, and threats Pulau Lengkang faces in its development into a renowned tourist hub, with a focus on the challenges of overcrowding and the potential for sustainable tourism. The study employs a qualitative approach, relying on thorough literature review to understand the island's unique cultural and historical aspects and the implications of increasing visitor numbers on its heritage and environment. The findings reveal that while Pulau Lengkang boasts significant cultural and historical appeal, overcrowding threatens to strain its infrastructure and dilute its heritage. However, opportunities for sustainable tourism and cultural preservation present viable pathways to enhance its tourism appeal and support local community well-being. The study suggests that adopting eco-tourism and cultural engagement strategies can help safeguard Pulau Lengkang's heritage and promote sustainable development.